Endovascular management of ischemic stroke a case-based approach - Pereira, Vitor Mendes; Dmytriw, Adam A.; Slater, Lee-Anne; Power, Sarah, 1976-; Krings, Timo (Thieme, 2021)
"Stroke is the most prevalent cerebrovascular emergency, impacting an estimated 15 million people worldwide every year. Endovascular treatment (EVT) of ischemic stroke has expanded at an unforeseen pace, with EVT the most common neurointerventional procedure performed at most large centers. Endovascular Management of Ischemic Stroke: A Case-Based Approach by renowned stroke pioneer Vitor Mendes Pereira and distinguished co-editors features contributions from a "who's who" of global experts. This practical resource provides straightforward guidance for clinicians who need to learn and master state-of-the-art endovascular interventions reflecting the new, evidence-based treatment paradigm for acute stroke"--